1996
DOI: 10.1002/(sici)1097-4652(199612)169:3<509::aid-jcp11>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

24,25-(OH)2D3 regulates protein kinase C through two distinct phospholipid-dependent mechanisms

Abstract: We have previously shown that 24,25-(OH)2D3 plays a major role in resting zone (RC) chondrocyte differentiation and that this vitamin D metabolite regulates protein kinase C (PKC). The aim of the present study was to identify the signal transduction pathway used by 24,25-(OH)2D3 to stimulate PKC activation. Confluent, fourth passage RC cells from rat costochondral cartilage were used to evaluate the mechanism of PKC activation. Treatment of RC cultures with 24,25-(OH)2D3 for 90 min produced a dose-dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…24R,25(OH) 2 D 3 increases the abundance of diacylglycerol (DAG) [6], an activator of many PKC isoforms. PKC activation by 24R,25(OH) 2 D 3 is maintained in the presence of chemical inhibitors targeted against either phosphatidylcholine (PC)-or phosphatidylinositol (PI)-specific phospholipase C (PLC) [7], indicating that the source of DAG is not due to the action of this enzyme.…”
Section: Rapid Actions Of 24r25(oh) 2 D 3 In the Resting Zonementioning
confidence: 99%
See 3 more Smart Citations
“…24R,25(OH) 2 D 3 increases the abundance of diacylglycerol (DAG) [6], an activator of many PKC isoforms. PKC activation by 24R,25(OH) 2 D 3 is maintained in the presence of chemical inhibitors targeted against either phosphatidylcholine (PC)-or phosphatidylinositol (PI)-specific phospholipase C (PLC) [7], indicating that the source of DAG is not due to the action of this enzyme.…”
Section: Rapid Actions Of 24r25(oh) 2 D 3 In the Resting Zonementioning
confidence: 99%
“…PKC activation by 24R,25(OH) 2 D 3 is maintained in the presence of chemical inhibitors targeted against either phosphatidylcholine (PC)-or phosphatidylinositol (PI)-specific phospholipase C (PLC) [7], indicating that the source of DAG is not due to the action of this enzyme. Inhibition of tyrosine kinase signaling also does not attenuate rapid actions of 24R,25(OH) 2 D 3 , eliminating tyrosine kinases as a source of PKC activation [6]. Instead, activation of PKC by 24R,25(OH) 2 D 3 is dependent upon DAG derived from phosphatidic acid (PA) generated the actions of by phospholipase D (PLD), specifically PLD2 [8,9].…”
Section: Rapid Actions Of 24r25(oh) 2 D 3 In the Resting Zonementioning
confidence: 99%
See 2 more Smart Citations
“…(1) It regulates membrane phospholipid metabolism through down-regulation of PLA 2 (8) and up-regulation of phospholipase D. (17) This results in changes in AA turnover and release and production of prostaglandin E 2 (9) and DAG. (18) It has been proposed that the rapid, membrane-mediated effects of 1,25(OH) 2 D 3 are mediated through the VDR after the latter is translocated to the cytoplasmic membrane. (19,20) Other reports suggested that specific membrane receptors exist for 1,25(OH) 2 …”
Section: Introductionmentioning
confidence: 99%